Wpływ Polski na utworzenie Związku Sowieckiego - Borzęcki, Jerzy (1956– ) (Instytut Historii PAN, 2024)
The article aims to show that Polish pressure on Soviet Ukraine and Soviet Belarus was an indirect but important factor in the creation of the Soviet Union. It also describes Moscow’s plans and calculations regarding foreign and domestic policy.
p. 5-31
Summary in English.
Keywords: Soviet Union; Poland; Ukraine; Belarus; Lenin, Vladimir Il'ič (1870-1924); Poland - foreign relations - Soviet Union - 1900-1945; Soviet Union - foreign relations - Poland - 1900-1945; Soviet Union - politics and government - 1917-1936